Punitive Irrationality in Ecuador: A Critical View from the Point of View of Penal Guaranty. - Alvaracín Jarrín, Adrián Alejandro (2023)
This research addresses, from the perspective of criminal guaranty, what I have called punitive irrationality, a term that refers to a heterogeneous set of punitive practices that affect the constitutional purposes of the penal system. In this way, prison conditions in the country are investigated, as well as the implications of punitive practices of an authoritarian nature in juvenile criminal justice. The examination of the background of these punitive practices allowed us to set two specific objectives that are developed in this research work. The first objective reveals the reasons for choosing the guarantor paradigm as a way out of the violent situation in which criminal justice in general is immersed, in such a way that a punitive or repressive approach is excluded. The second objective raises the need to contain this punitive irrationality through respect for human rights. Both objectives are of a critical-reflexive nature. In order to achieve them, the guarantees of fundamental rights were used, within the guarantee paradigm of penal minimalism or minimum penal law. In the methodological part, the documentary research technique is applied, in order to investigate in the texts the causes of this irrationality, which allows us to discover several of the critical knots that cause the crisis in the sphere of the penal system. In this way, it becomes evident that punitive irrationality is usually, among other factors, a consequence of the increase in the prison population, punitive practices on adults and adolescents, as well as the anti-guarantist view that disrespects fundamental guarantees, prevailing the need to implement the model of criminal guaranties to safeguard human dignity.